MODEL PJBL BERBANTUAN MEDIA INFOGRAFIS DALAM PEMBELAJARAN P5 TEMA KEARIFAN LOKAL MELALUI KEBUN SEKOLAH MINI DI SDN ROWOTENGAH 03 - Ririn Nurbaidah; Sudarti; Rusdhianti Wuryaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Abstract: This study aims to explore the implementation of the Project-Based Learning (PjBL) model assisted by infographic media in teaching, focusing on achieving the characteristics of the Pancasila Student Profile (P5) with the theme of Local Wisdom, through the management of a mini school garden at SDN Rowotengah 03. The research subjects involved 29 students using a qualitative approach to collect data from participatory observation, interviews, and document analysis. The PjBL model was applied to provide a student-centered learning experience, where they actively participated in the planning, implementation, and evaluation of the mini school garden project. Infographic media was used as an aid to visualize information about types of plants, plant life cycles, farming techniques, and the benefits of the mini school garden. The research results show that the application of the PjBL model assisted by infographic media was effective in enhancing the achievement of the six character dimensions of P5: having faith, piety to God Almighty, and noble character; global diversity; cooperation; independence; creativity; and critical thinking. Students demonstrated increased participation and engagement in learning, as well as a deeper understanding of local wisdom and agricultural practices. The implications of this research are the importance of integrating infographic media technology in project-based learning to strengthen student character in accordance with the Pancasila Student Profile, increase their engagement, enrich learning experiences, and promote understanding of environmental sustainability and social responsibility.